Institutionalization of Islam and Adat: The Legal System of Hak Langgeih in Aceh - Duhriah Duhriah; Fauzi Yati; Tezi Asmadia; Aulia Rahmat; Muslim Muslim; Ahmad Syukran Baharuddin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to discuss the institutionalization of custom and Islam in the Fatwa of Aceh’s Ulama Consultative Council (MPU). Local genius and adat have recently emerged as essential role of the legal pluralism discourse in the age of globalization. This fatwa was issued in an effort to preserve Muslim land and property ownership in Aceh, Indonesia, after the tsunami. The effort has its dynamics, considering the existence and control of property by non-Muslims. The problem in this study is how the dynamics of the legal system, encompassing legal substance, legal structure, and legal culture, interact with the institutionalization of legal rights in Aceh's MPU Fatwa. This research is socio-legal research. The results of this study indicate that adherence to adat, mediated by ‘hak mieung’, has placed adat structures as dispute resolution processes. Legal culture is of greater significance than legal structure and substance in the institutionalization of hak langgeih in Aceh.